2010
DOI: 10.1021/la102449m
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Organo Cobalt−Aluminum Layered Double Hydroxide via a Novel Single-Step Self-Assembling Method and Its Use as Flame Retardant Nanofiller in PP

Abstract: Synthesis of polypropylene/organo-layered double hydroxide (PP/OLDH) has been carried out based on self-assembled organocobalt-aluminum LDH (O-CoAl-LDH). The novel method of synthesizing self-assembled CoAl-LDH and its characterization have also been reported in details. This method is proven to be very efficient way of producing OLDH in a single step with homogeneous composition and structure. As flame-retardant nanofiller, O-CoAl-LDH shows significant decrease in heat release rate (HRR), the total heat relea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
120
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 156 publications
(126 citation statements)
references
References 42 publications
(26 reference statements)
4
120
0
Order By: Relevance
“…In all the spectra, an intense and broad adsorption band at 3359-3436 cm -1 corresponds to the stretching vibration of hydrogen bonded hydroxyl groups (ν O-H ) from all the samples. [28][29][30][31][32][33][34] The O-H bending vibration of the interlayer water is also observed at 1620-1650 cm -1 and 1589-1596 cm -1 for the product A-Co-Ni H prepared at starting ratio of 1:1 and all the EG-Co-Ni LDHs, respectively. After all, part of water can still intercalate into the layer of the samples due to the mixtured reaction system of EG and water.…”
Section: Resultsmentioning
confidence: 87%
“…In all the spectra, an intense and broad adsorption band at 3359-3436 cm -1 corresponds to the stretching vibration of hydrogen bonded hydroxyl groups (ν O-H ) from all the samples. [28][29][30][31][32][33][34] The O-H bending vibration of the interlayer water is also observed at 1620-1650 cm -1 and 1589-1596 cm -1 for the product A-Co-Ni H prepared at starting ratio of 1:1 and all the EG-Co-Ni LDHs, respectively. After all, part of water can still intercalate into the layer of the samples due to the mixtured reaction system of EG and water.…”
Section: Resultsmentioning
confidence: 87%
“…The reason could be that LDH has a role for catalytic degradation of PP. This means LDH does not improve the thermal stability of the matrix; it rather changes the decomposition mechanism of PP [12].…”
Section: Combustion Behaviors Of Pp/o-mgal-ldh Micro-nanocomposite Inmentioning
confidence: 98%
“…Therefore, LDH has attracted considerable attention as a flame retardant and thermal stabilizer [30][31][32][33][34][35][36][37][38]. In particular, Wang et al confirmed that MgAl LDH and CoAl LDH can efficiently improve the flame retardancy of PP [39,40]. In addition, the Ni-based LDH' catalysts are highly active and cost-effective in the partial oxidation and steam reforming of methane to produce H 2 [41,42].…”
Section: Introductionmentioning
confidence: 99%